PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA SEKTOR LAYANAN PERDAGANGAN DAN INVESTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - reny aziatul pebriani; Muhammad Hamdan Sayadi; Rafika Sari (Fakultas Ekonomi Universitas IBA, 2023)
This study aims to inspect the effect of tax planning and deferred tax burden on earnings management in the service, trade, and investment sectors listed on the Indonesia Stock Exchange for the period 2017-2021. The sample was selected using a purposive sampling technique. The sample in this study consisted of 62 companies engaged in the service, trade, and investment sectors that published their financial reports in 2017-2021. Furthermore, the data were analyzed using multiple linear regression. The result evinces that the tax planning variable has a positive effect on earnings management variables. However, the deferred tax expense variable is not proven to have a positive effect on earnings management variables. The results of the analysis show that simultaneously the tax planning variable and deferred tax expense have a positive effect on earnings management in the service, trade, and investment sectors